Antifibrotic Therapies and Progressive Fibrosing Interstitial Lung Disease (PF-ILD): Building on INBUILD - Shumar, John N. (J Clin Med, 2021)
Progressive fibrosing interstitial lung disease (PF-ILD) describes a phenotypic subset of interstitial lung diseases characterized by progressive, intractable lung fibrosis. PF-ILD is separate from, but has radiographic, histopathologic, and clinical similarities to idiopathic pulmonary fibrosis. Two antifibrotic medications, nintedanib and pirfenidone, have been approved for use in patients with idiopathic pulmonary fibrosis. Recently completed randomized controlled trials have demonstrated the clinical efficacy of antifibrotic therapy in patients with PF-ILD. The validation of efficacy of antifibrotic therapy in PF-ILD has changed the treatment landscape for all of the fibrotic lung diseases, providing a new treatment pathway and opening the door for combined antifibrotic and immunosuppressant drug therapy to address both the fibrotic and inflammatory components of ILD characterized by mixed pathophysiologic pathways.